Coyote scat in cities increases risk of human exposure to an emerging zoonotic disease in North America - Raymond, Sage; Steckler, Deanna K.; Seguin, M. Alexis; St. Clair, Colleen Cassady (Frontiers in Conservation Science, 2024)
Zoonoses associated with urban wildlife are increasingly concerning for human health and include the recent emergence of alveolar echinococcosis (AE) in North America. AE develops following infection with the tapeworm Echinococcus multilocularis. In Alberta, >50% of urban coyotes (Canis latrans) are infected with E. multilocularis, and infected scats contain eggs that can be accidentally ingested by people. We aimed to determine the predictors of infection prevalence and intensity in coyote scats in Edmonton, Canada, and to identify the predictors of scat deposition and content, especially as related to anthropogenic food sources and infrastructure. To study infection prevalence and intensity, volunteers collected 269 scats, which were tested for E. multilocularis using polymerase chain reaction. We compared infection prevalence and shedding intensity by habitat and scat content. To determine predictors of scat presence and content, we identified 1263 scats using snow tracking. We compared landscape characteristics at scats and available points, and among scats with different contents. We used negative binomial regression to predict scat abundance in city-delineated green spaces. 26.0% of tested scats were positive for E. multilocularis (n = 70), and infection was twice as common as expected near compost and 1.3x more common than expected when scats contained anthropogenic food. Scats were more common than expected near other scats (80% within 1 m of scats, 27% at 11.5 m), buildings (19% at buildings, 16% at 80 m), and the camps of people experiencing homelessness (24% at camps, 20% at 60 m). Scats frequently contained fruit (52.9%), anthropogenic material (36.7%), and birdseed (16.0%), and scats containing anthropogenic material often occurred near human infrastructure, supporting a relationship between anthropogenic attractants and scat accumulation. These results suggest that abundant food sources and anthropogenic food increase coyote aggregation, increasing both scat abundance and infection rates, which in turn increases risk of exposure to zoonotic parasites for humans. Risk to humans might be reduced by preventing coyote access to anthropogenic and This is a provisional file, not the final typeset article aggregated food sources and educating people who are likely to encounter infected soil or vegetation, including gardeners, park users, and people experiencing homelessness.